The quality of Haemoglobin examination results with variations in incubation time using the Cyanmethemoglobin method - Ellies Tunjung; Fitrotin Azizah; Vella Rohmayani; Baterun Kunsah; Rizka Vera Yunia (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2020)
Anaemia is a condition where blood red blood levels or haemoglobin is lower than normal values. More than 50% of cases of anaemia are spread throughout the world. One of checks to diagnose anaemia is examination of haemoglobin levels. Examination of haemoglobin levels can be determined by several methods, namely the Sahli’s method, the Cyanmethemoglobin method manually and by automatic method. Examination of haemoglobin levels with a of more than 5 minutes incubation time leads to inaccurate results. The purpose of this research is to determine the effect of incubation time on the results of haemoglobin level examination of the Cyanmethemoglobin method. This type of research is experimental research to determine the effect of the incubation time on the results of haemoglobin level examination of the Cyanmethemoglobin method. The population in this research is outpatients with a diagnosis of kidney failure at Gatoel Hospital, Mojokerto, in March 2019. The number of examination samples is 9 samples which is carried out at the Gatoel Hospital Laboratory, Mojokerto. The results of this research show that the average haemoglobin incubation rate of 5 minutes is 7,52 g/dl, incubation of 20 minutes is 7,18 g / dl, and incubation of 30 minutes is 7,04 g / dl. The conclusion of this research is that there is no effect on the delay in incubation time on the results of the haemoglobin level examination of the Cyanmethemoglobin method.